Penerapan Algoritma Sequential Insertion Dalam Pendistribusian BBM di Kawasan TImur Indonesia (Studi Kasus Pada PT. Pertamina UPMS VIII Terminal Transit Wayame-Ambon) - D. B. Paillin; Erlon Wattimena (ARIKA, 2015)
Problems distribution where the transport vehicle departs from depot to get to some destination point by passing through multiple routes and come back to the same depot better known as the Vehicle Routing Problem ( VRP ) . VRP is an NP - hard problem Combinatorial means more size or variable problem, efforts to make computing will also increase exponentially. This is the background of this research by applying algorithms Sequential Insertion resolve the problems of VRP to determine the optimum (minimum of vehicles and duration ) in the distribution of fuel in the eastern region of Indonesia with the characteristics of VRP with heterogeneous fleet of vehicles , VRP with multiple trips , VRP with split deliveries, VRP with multiple products and multiple compartements.